2004
DOI: 10.1101/gad.1178004
|View full text |Cite
|
Sign up to set email alerts
|

Loss of cell polarity causes severe brain dysplasia in Lgl1 knockout mice

Abstract: Disruption of cell polarity is seen in many cancers; however, it is generally considered a late event in tumor progression. Lethal giant larvae (Lgl) has been implicated in maintenance of cell polarity in Drosophila and cultured mammalian cells. We now show that loss of Lgl1 in mice results in formation of neuroepithelial rosette-like structures, similar to the neuroblastic rosettes in human primitive neuroectodermal tumors. The newborn Lgl1 −/− pups develop severe hydrocephalus and die neonatally. A large pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
336
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(349 citation statements)
references
References 49 publications
13
336
0
Order By: Relevance
“…Although it is possible that NMHC II-B serves as a downstream target of aPKC in regulating cell adhesion in the spinal canal, there are other putative targets in the neuronal adherens junction as well, such as PAR3 and Lgl1 (Yamanaka et al, 2003;Klezovitch et al, 2004;Suzuki and Ohno, 2006;Vasioukhin, 2006). In contrast, Even-Faitelson and Ravid (2006) have reported that phosphorylation of the NMHC II-B in the nonhelical tail by an aPKC results in cortical localization of both NM II-B and aPKC in a prostate cancer cell line.…”
Section: Cell-cell Adhesion Of the Neuroepithelial Cells Requires Nonmentioning
confidence: 97%
“…Although it is possible that NMHC II-B serves as a downstream target of aPKC in regulating cell adhesion in the spinal canal, there are other putative targets in the neuronal adherens junction as well, such as PAR3 and Lgl1 (Yamanaka et al, 2003;Klezovitch et al, 2004;Suzuki and Ohno, 2006;Vasioukhin, 2006). In contrast, Even-Faitelson and Ravid (2006) have reported that phosphorylation of the NMHC II-B in the nonhelical tail by an aPKC results in cortical localization of both NM II-B and aPKC in a prostate cancer cell line.…”
Section: Cell-cell Adhesion Of the Neuroepithelial Cells Requires Nonmentioning
confidence: 97%
“…In this mouse, the apical delivery of some proteins, including N-cadherin and aPKC, is impaired resulting in a premature depletion of the stem/precursor pool within the VZ and a consequent reduction of cortical thickness. In addition, disruption of cell polarity and associated loss of AJs in Lgl1 knockout mice result in the appearance of rosettes of mislocalized proliferating stem/precursor cells in areas normally occupied by more differentiated cells (Klezovitch et al, 2004). Such rosettes are also seen in a Kap3 knock-out mouse (Kap3 being part of the Kif3 molecular motor complex), where the delivery of N-cadherin protein at the plasma membrane is impaired (Teng et al, 2005).…”
Section: Similarities and Differences Between Adult And Fetal Neural mentioning
confidence: 99%
“…The adenomatous polyposis coli (APC) gene is required for the asymmetric division of Drosophila spermatogonial stem cells and it is also a critical tumour suppressor in human colon cancer [112][113][114] . A human homologue of the Drosophila gene LgL is HUGL1, which controls cell polarity and is commonly inactivated in cancer in humans and in mice [115][116][117] . Last, inactivation of Numb may in turn activate the Notch signalling pathway, commonly observed in human solid and hematopoietic tumors 118,119 .…”
Section: Asymmetric Division Of Stem Cells and Cancermentioning
confidence: 99%